Steam kids : 50+ science, technology, engineering, art, math hands-on projects for kids - Carey, Anne, ....-; Dziengel, Ana, ....-; Scardino, Amber, ....- (S.l. : CreateSpace Independent Publishing Platform, 2016)
A year's worth of captivating STEAM (Science, Technology, Engineering, Art & Math) activities that will wow the boredom right out of kids! Created by an MIT engineer, award winning educators, designers, and homeschooling experts, STEAM Kids will inspire your children to: question like a scientist design like a technologist build like an engineer create like an artist deduce like a mathematician – and, most importantly – play like a kid! Inside you'll find entertaining and educational projects like: - Rainbow Reactions - PVC Pipe Slingshot - Grafitti Art & Science - Color Changing Play Dough - Diaper Science - Circuit Bugs - Candy Mazes & so much more! Perfect for children ages 4-10, all the step-by-step activities are helpfully coded with difficulty indicators and estimated project times. Helpful project extensions promote further exploration and learning for enthusiastic children. Bonus materials will make things easy for parents and educators, and include: a handy weekly planning guide, project shopping lists, STEAM journal and more.